CONCERNING POETRY AND FICTION (LYRICS AND EPICS) AS TWO FORMS OF CRITICAL INITIATION AND INSPIRATION IN DEALING WITH LITERATURE - Fedor Matejov (Slovenska Literatura, 2009)
This reflection is a short summary of reading and partly a work experience with the texts devoted to Slovak literature. They come approximately from the half of the last century. This experience points the title of formulated thesis. It also vouched it by enumeration of the relevant key names from that aspect and gestures coming from the Modernism of the beginning century, mainly from the 30-tieth and the 40-tieth throughout the 60-tieth and after the 70-tieth and the 80-tieth. Writing about poetry was particularly focused on older line personalized (empathic or critically distant), and stressing more evocation of the work, dealing with the character of an author and methodically progressing a structural line. That is in inspirational confrontation with a transformation in poetry that happened in the end of the 50- tieth and the 60-tieth that evolved several interpretational initiatives concentrated semantically on complicated contemporary poetic texts. Fiction – in all transformations that modernized it – as it would correspondence more with all the more articulated constituted “worlds“ than contemporary poetry with intermediate self-understanding of society, with its official or alternative explanation if it is not considered naively only as an expression or a symptom with its the “world“ opening explosiveness, contemplativeness, fragmentariness, etc. Analogies of narrative fiction and historiography interpretation could help in a less conflicted transposed fiction into treating history of literature. An experience that makes rather problematic an usual work with literature of a strong poetry sort can serve as a reminder: history is not only stated by “subsequence “and “similarity “of facts (in all methodological travesties still always of Comte´s provenience), but it has non spectacular dimension “in actu“ evolving semantic ruptures, explosions, epiphanies, illuminations, or catastrophes – just a way of articulation, happening, “work“ of lyric text.